Peritoneal Inclusion Cyst with Entrapped Ovarian Syndrome: A Case Report - Depar, Asma Ali; Dhanwani, Anny; Majeed, Aiman; Rehman, Aimen; Khan , Rozilla Sadia (Indus Journal of Bioscience Research, 2025)
Peritoneal inclusion cysts or pseudocysts of the peritoneum, are uncommon and noncancerous cystic growths that occur due to chronic irritation of the peritoneal lining, frequently developing after pelvic surgery, or as a sequela of surgical inflammation. We report the case of a 42-year-old female with a chronic history of abdominal surgeries who presented with chronic pelvic pain and bilateral flank pain. Other imaging studies showed a large multiloculated cyst in the vicinity of the ovary, periovarian cyst. She received hormonal therapy without relief. Surgical treatment was needed. Diagnosis was made during laparotomy and bilateral oophorectomy, which revealed PICs with Entrapped Ovary Syndrome. The patient's postoperative recovery was successful, and histopathology confirmed benign features. This case highlights the diagnostic challenges of PICs, the need for multimodal imaging in complex presentations, and underscores the importance of individualized surgical management, especially in patients with extensive adhesions or atypical clinical symptoms